2007
DOI: 10.3168/jds.2007-0100
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Demand Affects Ruminal Digestion Responses to a Change in Dietary Forage Concentration

Abstract: Previous research in our laboratory has indicated that the physical filling effects of high-forage diets become increasingly dominant in determining feed intake and milk production as nutrient demand increases. This effect was tested further by using 14 ruminally and duodenally cannulated Holstein cows in a crossover design experiment with a 14-d preliminary period and two 15-d experimental periods. During the preliminary period, 3.5% fat-corrected milk yield was 15 to 60 kg/d (mean = 40 kg/d), and preliminary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…Few studies in the literature report rates of passage of various size particles for iNDF and pdNDF fractions. In a study using the same method as the one used in this experiment, passage rate of iNDF was greater than pdNDF for particles <2.36 mm for cows fed low-fiber or high-fiber diets including alfalfa silage and corn silage as forage sources (Voelker Linton and Allen, 2007). Another study reported faster passage rates for iNDF than pdNDF for particles <2.50 mm for cows fed a mixed timothy and meadow fescue grass silage, but that study used rumen evacuations and fecal output, rather than duodenal flow, to calculate passage rates (Rinne et al, 2002).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Few studies in the literature report rates of passage of various size particles for iNDF and pdNDF fractions. In a study using the same method as the one used in this experiment, passage rate of iNDF was greater than pdNDF for particles <2.36 mm for cows fed low-fiber or high-fiber diets including alfalfa silage and corn silage as forage sources (Voelker Linton and Allen, 2007). Another study reported faster passage rates for iNDF than pdNDF for particles <2.50 mm for cows fed a mixed timothy and meadow fescue grass silage, but that study used rumen evacuations and fecal output, rather than duodenal flow, to calculate passage rates (Rinne et al, 2002).…”
Section: Resultsmentioning
confidence: 85%
“…Reduction of particle size during eating is included in the rate of particle size reduction (k r ). Passage rates (k pi ) are calculated for indigestible NDF (iNDF) and potentially digestible NDF (pdNDF); k r is calculated for iNDF only.Figure reprintedwith permission from Voelker Linton andAllen (2007).…”
mentioning
confidence: 99%
“…A meta-analysis reported by Ferraretto et al (2013) determined that DMI was not altered by dietary starch content, milk yield increased by 0.08 kg/d for every percentage unit increase in dietary starch; however, this did not result in altered efficiency of feed conversion. Replacement of the rapidly fermentable carbohydrates provided by corn grain with fermentable carbohydrates from NFFS has resulted in little alteration in milk or milk component production (Voelker Linton and Allen, 2007;Gencoglu et al, 2010). In summary, substitution of wheat middlings and beet pulp for corn grain resulted in similar lactational performance for cows at high DMI and milk production levels.…”
Section: Lactation Performancementioning
confidence: 96%
“…Feed and duodenal digesta samples were collected during a research project conducted at Michigan State University (East Lansing, MI) following approval by the Institutional Animal Care and Use Committee (Voelker Linton and Allen, 2007). Prior to calving, 14 multiparous Holstein cows from the Dairy Cattle Teaching and Research Center were equipped with rumen and duodenal cannulas and housed in tie stalls.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Daily intakes of each vitamin were calculated as the concentration of each vitamin in the TMR multiplied by DMI. Calculations of DM DF were described by Voelker Linton and Allen (2007). Duodenal flow was calculated as B-vitamin concentrations in the duodenal sample multiplied by the daily DM flowing through the duodenum.…”
Section: Calculations and Statistical Analysesmentioning
confidence: 99%